The Role of Guidance Counselors in The Language Development of Young Children - Annisa Ramadhani; Nur Khadijah; Zahra Mardatillah; Rezi Maswar; Roni Pasaleron; Sabiruddin Sabiruddin (Suluah Pasaman, 2025)
The purpose of this article is to identify variables that influence early childhood language development. A literature review approach was used in this study to determine the elements that influence early childhood language development. The findings of this study indicate that language development in early childhood begins at birth and develops through experience and expertise. The language and communication development of early childhood is greatly influenced by internal and external factors. Internal factors include genetic characteristics, gender, health, and intelligence. External factors include social relationships, parental education, family economic status, and family dynamics. The role of counseling guidance in early childhood language development is to help children develop language and communication skills, identify and overcome children's language difficulties, provide support and guidance to parents, integrate language guidance programs into learning activities, and monitor children's language development and provide intervention if necessary.